Mechanical thrombectomy in patients with acute ischemic stroke and lower nihss scores: recanalization rates, periprocedural complications, and clinical outcome - Pfaff, Johannes; Herweh, Christian; Pham, Mirko; Schönenberger, Silvia; Nagel, Simon; Ringleb, Peter A.; Bendszus, Martin; Möhlenbruch, Markus Alfred (American journal of neuroradiology, 2016)
BACKGROUND AND PURPOSE: Mechanical thrombectomy, in addition to intravenous thrombolysis, has become standard in acute ischemic stroke treatment in patients with large-vessel occlusion in the anterior circulation. However, previous randomized controlled stroke trials were not focused on patients with mild-to-moderate symptoms. Thus, there are limited data for patient selection, prediction of clinical outcome, and occurrence of complications in this patient population. The purpose of this analysis was to assess clinical and interventional data in patients treated with mechanical thrombectomy in case of ischemic stroke with mild-to-moderate symptoms. - MATERIALS AND METHODS: We performed a retrospective analysis of a prospectively collected stroke data base. Inclusion criteria were anterior circulation ischemic stroke treated with mechanical thrombectomy at our institution between September 2010 and October 2015 with an NIHSS score of ≤8. - RESULTS: Of 484 patients, we identified 33 (6.8%) with the following characteristics: median NIHSS = 5 (interquartile range, 4-7), median onset-to-groin puncture time = 320 minutes (interquartile range, 237-528 minutes). Recanalization (TICI = 2b-3) was achieved in 26 (78.7%) patients. Two cases of symptomatic intracranial hemorrhage were observed. Favorable (mRS 0-2) and moderate (mRS 0-3) clinical outcome at 90 days was achieved in 21 (63.6%) and 30 (90.9%) patients, respectively. - CONCLUSIONS: The clinical outcome of patients undergoing mechanical thrombectomy for acute ischemic stroke with mild stroke due to large-vessel occlusion appears to be predominately favorable, even in a prolonged time window. However, although infrequent, angiographic complications could impair clinical outcome. Future randomized controlled trials should assess the benefit compared with the best medical treatment.
Gesehen am 13.10.2020